Falling Through the Cracks: Academic and Career Challenges Faced by Immigrant Graduate Students - Sinacore, Ada L.; Park, Jeeseon; Mikhail, Anne Marie; Wada, Kaori (Canadian Journal of Counselling and Psychotherapy, 2011)
The goals of this study are twofold. First, it aims to understand immigrant graduate students’ experiences in higher education and how these influence cultural transitioning and social integration to Quebec society. Second, the study examines the career counselling and mentoring needs of immigrant graduate students while attending university. Implications and recommendations for career counselling and mentoring programs are discussed.